2022
DOI: 10.3390/jof8050431
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Factors Affecting Diversity, Structure, and Temporal Variation of Airborne Fungal Communities in a Research and Teaching Building of Tianjin University, China

Abstract: Airborne fungi are widely distributed in the environment and may have adverse effects on human health. A 12-month survey on the diversity and concentration of culturable airborne fungi was carried out in a research and teaching building of Tianjin University. Indoor and outdoor environments were analyzed using an HAS-100B air sampler. A total of 667 fungal strains, belonging to 160 species and 73 genera were isolated and identified based on morphological and molecular analysis. The most abundant fungal genera … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 101 publications
2
16
2
Order By: Relevance
“…In addition, our results also showed that the fungal diversity was positively correlated to the temperature at the 3CO (* P < 0.05). This observation is consistent with previous studies that described temperature and humidity playing important roles in the airborne fungal distribution and diversity ( Hoyos et al, 1998 ; Fang et al, 2005 ; Lu et al, 2022 ). In summary, the analyses performed in our work revealed a remarkable fluctuation in the fungal diversity of every sampling site at different seasons.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, our results also showed that the fungal diversity was positively correlated to the temperature at the 3CO (* P < 0.05). This observation is consistent with previous studies that described temperature and humidity playing important roles in the airborne fungal distribution and diversity ( Hoyos et al, 1998 ; Fang et al, 2005 ; Lu et al, 2022 ). In summary, the analyses performed in our work revealed a remarkable fluctuation in the fungal diversity of every sampling site at different seasons.…”
Section: Discussionsupporting
confidence: 93%
“…In the latter study, Alternaria , Aspergillus , and Cladosporium were reported to be responsible for allergic rhinitis or asthma ( Shelton et al, 2002 ). Previous studies have shown that the concentrations of the airborne fungi are influenced by local environmental variables, fungal substrates, and human activities ( Banerjee et al, 1987 ; Hameed and Khodr, 2001 ; Lu et al, 2022 ). Researchers have demonstrated that indoor and outdoor diversity and concentration of fungal spores vary throughout the day depending on weather parameters ( Rodriguez-Rajo et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…The remarkably dominant presence in the air of Alternaria viable particles during spring could be explained by the simultaneous large availability of newly emerged plant organs, particularly leaves, in this season, given that Alternaria fungi are recognized as common plant pathogens ( Rotem, 1994 ). In a previous study performed by our research group on the indoor airborne fungal communities in a research and teaching building of Tianjin University ( Lu et al, 2022 ), it was hypothesized that the high concentration of Alternaria fungi recorded both inside and outside the investigated building could be sustained by long distance transport of Alternaria conidia originating from crops and orchards situated in the surrounding territory of Tianjin. Similarly, the atmospheric concentration of Alternaria spores in Badajoz, South-west Spain, was correlated to different types of agricultural land in the surrounding areas ( Fernández-Rodríguez et al, 2014 ), while airborne microbial communities in a mid-altitude mountain area of France showed increased relative abundance of fungal phytopathogens and leaf-associated fungi during the spring and summer periods when the crop plants grew and trees were green ( Tignat-Perrier et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to Awad (2002) , one of the most significant sources of fungal air contamination is vegetation, while several studies showed a significant influence of air pollution on fungal diversity and concentration, although with controversial results ( Dong et al, 2016 ; Yan et al, 2016 ; Zhou et al, 2021 ; Lu et al, 2022 ). In this study, we attempted to better understand the influence of vegetation presence and air pollution on airborne fungi in urban environments, by comparing the structure of the fungal communities present in green vs. busy areas, in different Tianjin districts.…”
Section: Discussionmentioning
confidence: 99%
“…In the same season, the concentrations of airborne bacteria and fungi in the air were different from each site, which may be related to microenvironmental conditions, human activity, ventilation systems, different substrata, etc. ( Tanaka et al, 2015 ; Lu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%